SCIENTIFIC WRITING ABILITY IN STUDENTS INDONESIAN LANGUAGE AND LITERATURE EDUCATION - nurfidah, nurfidah; Rosdiyanti, Evi (Jurnal Ilmiah Mandala Education (JIME), 2022)
Writing scientific papers, students often have difficulty mastering vocabulary and grammar. Difficulty in getting ideas or ideas has always been an obstacle, even though in writing a scientific paper the author is required to have ideas or ideas as well as adequate vocabulary and relate to the theme that will be raised in writing. This study aims to describe the ability to write scientific papers in students of the Indonesian language and literature study program STKIP Harapan Bima. The type of research used descriptive qualitative. The samples used in this study were 11 students of the third semester of the Indonesian Language and Literature Education Study Program. The data collection techniques through interview, observation, and documentation of students work. Data analysis is the process of systematically searching and compiling data sequences, data obtained from interviews, field notes, and documentation, by organizing data into categories, describing them into units, synthesizing, arranging into patterns, and choosing which ones are important. What will be studied, and then make conclusions so that they are easily understood by themselves and others. Based on the results of data analysis, it can be concluded that the ability to write scientific papers toward students of the Indonesian Language and Literature Education study program STKIP Harapan Bima were declared unable.